(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
In May 2024, in Lisbon, the laboratory So That We Do Not Forget Our Descendance from the Child: co-movement, co-existence, and participation in the flow of life (and of the scene) was held, led by Tatiana Motta Lima. The artist-researcher Vitor Lemos took part in the laboratory as an observer. A few days later, the two met for a conversation, taking as their starting point the exercises, improvisations, and games proposed during the laboratory. The dialogue focused mainly on the search for the flow of life on stage. They discussed the artistic-pedagogical processes of both researchers, thereby developing new inquirires within each interlocutor´s laboratory practices.